Variations in the management of significant polyps and early colorectal cancer: results from a multicentre observational study of 383 patients. (6th August 2018) - Dattani, M.; Crane, S.; Battersby, N. J.; Di Fabio, F.; Saunders, B. P.; Dolwani, S.; Rutter, M. D.; Moran, B. J.; ,
Abstract: Aim: The concept of significant polyps and early colorectal cancer (SPECC) encompasses complex polyps not amenable to routine snare polypectomy or where malignancy cannot be excluded. Surgical resection (SR) offers definitive treatment, but is overtreatment for the majority which are benign and amenable to less invasive endoscopic resection (ER). The aim of this study was to investigate variations in the management and outcomes of significant colorectal polyps. Method: This was a retrospective observational study of significant colorectal polyps, defined as nonpedunculated lesions of ≥ 20 mm size, diagnosed across nine UK hospitals in 2014. Inclusion criteria were endoscopically or histologically benign polyps at biopsy. Results: A total of 383 patients were treated by primary ER (87.2%) or SR (12.8%). Overall, 108/383 (28%) polyps were detected in the Bowel Cancer Screening Programme (BCSP). Primary SR was associated with a significantly longer length of stay and major complications ( P < 0.01). Of the ER polyps, 290/334 (86.8%) patients were treated without undergoing surgery. The commonest indication for secondary surgery was unexpected polyp cancer, and of these cases 60% had no residual cancer in the specimen. Incidence of unexpected cancer was 10.7% ( n = 41) and was similar between ER and SR groups ( P = 0.11). On multivariate analysis, a polyp size of > 30 mm and non‐BCSP status were independent risk factors for primary SR [OR 2.51 (95% CI 1.08–5.82), P = 0.03]. Conclusion: ER is safe and feasible for treating significant colorectal polyps. Robust accreditation within the BCSP has led to improvements in management, with lower rates of SR compared with non‐BCSP patients. Standardization, training in polyp assessment and treatment within a multidisciplinary team may help to select appropriate treatment strategies and improve outcomes.